2019
DOI: 10.1111/jace.16792
|View full text |Cite
|
Sign up to set email alerts
|

High permittivity and excellent high‐temperature energy storage properties of X9R BaTiO3–(Bi0.5Na0.5)TiO3 ceramics

Abstract: We fabricated x(Bi0.5Na0.5)TiO3–(1−x)[BaTiO3–(Bi0.5Na0.5)TiO3–Nb] (BNT‐doped BTBNT‐Nb) dielectric materials with high permittivity and excellent high‐temperature energy storage properties. The initial powder of Nb‐modified BTBNT was first calcined and then modified with different stoichiometric ratios of (Bi0.5Na0.5)TiO3 (BNT). Variable‐temperature X‐ray diffraction (XRD) results showed that the ceramics with a small amount of BNT doping consisted of coexisting tetragonal and pseudocubic phases, which transfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…9 compares the energy storage efficiency and recoverable energy storage density of various lead-free ceramics that have potential for applications under medium-low electric fields. [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54] It can be seen that compared with other lead-free ceramics, 0.85BBNKT-0.15SMN ceramic has certain advantages over other lead-free ceramics in terms of overall energy storage performance.…”
Section: Energy Storage Properties Of Bbnkt-smn Ceramicsmentioning
confidence: 99%
“…9 compares the energy storage efficiency and recoverable energy storage density of various lead-free ceramics that have potential for applications under medium-low electric fields. [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54] It can be seen that compared with other lead-free ceramics, 0.85BBNKT-0.15SMN ceramic has certain advantages over other lead-free ceramics in terms of overall energy storage performance.…”
Section: Energy Storage Properties Of Bbnkt-smn Ceramicsmentioning
confidence: 99%
“…Core-shell structure with fingerprint-like nanodomains as core parts can be detected, as shown in the circled sites, but are not ubiquitous as typical core-shell structured systems such as BaTiO 3 based ceramics. 2,4 The relatively large | 5819 doping amount of the SrZrO 3 can lead to a large volume ratio of the shell part, causing the core part with ferroelectric domain stripes to be compressed to nanoscale. In addition, the detection of ferroelectric stripes in bright-field TEM image mode depends on the interaction angle between the incident electrons and the sample; therefore, the core-shell structure is not generally observed in every grain.…”
Section: Phase Structure and Microstructurementioning
confidence: 99%
“…Capacitors are widely used in industries such as aerospace and aviation, deep oil drilling, and the automotive industry, where the electronic equipment is usually subjected to high working temperatures. 1,2 For example, the temperature of the engine bay can reach approximately 150°C and the antiblock system is required to function from 150°C to 250°C in automotive industry. 1 In general, temperature-stable dielectric materials are critical for future development of these industries.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that adding a small amount of Nb 2 O 5 can suppress the dielectric peak of BNT-based ceramics and shift T m downward to low temperature, achieving TCC ± 0.15 standard in a wide temperature range. [35][36][37][38][39][40][41] Based on the above considerations, it is logical to explore Nb 2 O 5 addition in our previous optimized Ce 4+ -doped BNBST ceramics for boosting dielectric temperature stability and energy storage properties. x wt%Nb 2 O 5 , x = 0, 0.5, 1.0, 1.5, 2.0, 2.5, 3.0, 3.5, and 4.0) ceramics by a solid-state reaction method.…”
Section: Introductionmentioning
confidence: 99%
“…However, its relatively low recoverable energy density ( W rec ∼ 1.15 J/cm 3 ) needs to be further increased, and the window of temperature stability also needs to be further widened. Many studies have shown that adding a small amount of Nb 2 O 5 can suppress the dielectric peak of BNT‐based ceramics and shift T m downward to low temperature, achieving TCC ± 0.15 standard in a wide temperature range 35–41 . Based on the above considerations, it is logical to explore Nb 2 O 5 addition in our previous optimized Ce 4+ ‐doped BNBST ceramics for boosting dielectric temperature stability and energy storage properties.…”
Section: Introductionmentioning
confidence: 99%